The Relationship Between Risk-Taking Behavior Viewed From The Impulsivity And Mental Toughness Of Mountain Climbers - Mifrohul A'la; Rr Dwi Astuti (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Mountain climbing is a high-risk activity that demands good decision-making skills, self-regulation, and psychological readiness. The research uses a quantitative approach with a correlational method. The sampling technique used purposive sampling with the criteria that respondents are 18 years old and above and have a hobby of mountain climbing. The minimum sample size for the study was set at 68 participants based on G Power analysis. Data collection was conducted using a validated Likert scale, and data analysis was performed using two-predictor regression and product-moment correlation with the help of SPSS 27.0 for Windows. The research results show a very significant relationship between impulsivity and mental toughness with risk-taking behavior, with an R value of 0.792, an F value of 79.156, and a significance of 0.000 (p<0.01), as well as an effective contribution of 62.7%. Partially, impulsivity has a very significant positive relationship with risk-taking behavior with an R value of 0.776 and an effective contribution of 60.2%. Meanwhile, mental toughness has a very significant negative relationship with risk-taking behavior with an R value of -0.710 and an effective contribution of 50.4%. These findings indicate that the higher the impulsivity, the higher the risk-taking behavior, while the higher the mental toughness, the lower the tendency for risk-taking behavior.